Soil Characteristics of Chandars of Easters Uttar Pradesh - Banerjee, S. P.; Sharma, S. D. (Indian Forester, 1990)
The soils of the grassy blanks, locally known as Chandars of the pilibhit and South Kheri forests were studied to sort out the salient differences in their characteristics in relation to associated vegetation. The growth of the supported vegetation was found to be related to organic matter and clay content. Where texture is comparatively heavier, indicative of high moisture retention capacity, with pronounced translocation of clay resulting into argillic horizon, and availability of nutrients is high, the invasion of grasses by Shorea robusla and Colebrookia oppositifoloa is apparent. The grasses are tbe early colonizers and not the retrograded stage of vegetation. The soils of the sites have heen classified as Typic Ustipsamment,Entic Haplumbrept. Eutric Ustochrepts and Mollic Argiustalf.